Smoking is associated with higher risk of contracting bacterial infection and pneumonia, intensive care unit admission and death - Stattin, K; Eriksson, M; Frithiof, R; Kawati, R; Crockett, D; Hultström, M; Lipcsey, M (Public Library of Science, 2024)
Background: Smoking has been associated with a higher risk of contracting pneumonia, but contradictory results have shown that smoking may or may not decrease the risk of dying in pneumonia. The aim of this study is to investigate how smoking is associated with contracting any infection and pneumonia and death. Method and findings: Participants were drawn from the population-based Cohort of Swedish Men and the Swedish Mammography Cohort, which are representative of the Swedish population. Participants have answered detailed lifestyle questionnaires and have been followed in national registers, such as the Patient Register, Cause of Death register and Swedish Intensive Care Registry. The risks of contracting infection and pneumonia or dying in infection and pneumonia were assessed using Cox regression. Of 62,902 cohort participants, 25,297 contracted an infection of which 4,505 died; and 10,471 contracted pneumonia of which 2,851 died. Compared to never smokers, former smokers at baseline had hazard ratio (HR) 1.08 (95% confidence interval (CI) 1.05–1.12) of contracting and HR 1.19 (95% CI 1.11–1.28) of dying in infection and HR 1.17 (95% CI 1.12–1.23) of contracting and HR 1.16 (95% CI 1.06–1.27) of dying in pneumonia during follow-up. Compared to never smokers, current smokers at baseline had HR 1.17 (95% CI 1.13–1.21) of contracting infection and HR 1.64 (95% CI 1.52–1.77) dying in infection; HR 1.42 (95% CI 1.35–1.49) of contracting pneumonia and HR 1.70 (95% CI 1.55–1.87) of dying in pneumonia during follow-up. The risk of contracting and dying in infection and pneumonia increased in a dose-response manner with number of pack years smoked and decreased with years since smoking cessation. Conclusion: Smoking is associated with contracting and dying in any infection and pneumonia and the risk increases with pack years smoked, highlighting the importance of both primary prevention and smoking cessation.